Active Methodologies in Teaching Human Anatomy: An Integrative Review - de Lima, Paola; Guedert, Denis Guilherme; Silva, Renata Souza e; Cerqueira, Gilberto dos Santos (International Journal for Innovation Education and Research, 2021)
Human anatomy is one of the fundamental disciplines for the training of health professionals, especially in the medical field. Its didactic origin is based on the European school where the body was dissected in amphitheaters and anatomical knowledge was transmitted from the teacher to his students. With the restructuring of medical curricula, and the use of active methodologies, seeking to make the student the center of the learning process, anatomy started to be taught in another way. This study carries out an integrative review in the Scielo, Science Direct and Google Scholar databases, from 2015 to 2020, about the active methodologies used in the teaching of human anatomy for the medical course. The PICo strategy was used to form the guiding question and the results were presented through the Prisma Flow diagram. It was found that there are a number of tools and strategies that can be used aiming at the active teaching of human anatomy, however, a common point observed in most works is the approach of joint use with cadavers and anatomical parts, thus seeking to stimulate the development of the skills and competences of medical students.